2003
DOI: 10.1152/ajpgi.00094.2003
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal irradiation increases inflammatory cytokine expression and activates NF-κB in rat ileal muscularis layer

Abstract: The small bowel is an important dose-limiting organ in abdominal radiotherapy because irradiation can cause acute enteritis that, in turn, leads to progressively reduced motility and finally, in a later phase, to fibrosis. Because these clinical symptoms may be caused by the early stage of an inflammatory process, we characterized the radiation-induced intestinal inflammation in rats. Abdominal gamma-irradiation (10-Gy) induced a cascade of inflammatory events characterized by an early (6 h after exposure) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 49 publications
4
51
0
2
Order By: Relevance
“…Transcription factors also play an important role in the progression of the inflammatory lung response following irradiation [71,95,96]. Nuclear factor kappa B (NF-κB) has been shown to be continuously activated following irradiation and is involved in initiating and sustaining the inflammatory response [97,98].…”
Section: Lung Inflammation Post Irradiation (Pi) -Nf-κbmentioning
confidence: 99%
“…Transcription factors also play an important role in the progression of the inflammatory lung response following irradiation [71,95,96]. Nuclear factor kappa B (NF-κB) has been shown to be continuously activated following irradiation and is involved in initiating and sustaining the inflammatory response [97,98].…”
Section: Lung Inflammation Post Irradiation (Pi) -Nf-κbmentioning
confidence: 99%
“…These radiationinduced intestinal injuries thus continue to limit the effectiveness of radiotherapy (Andreyev, 2005). We previously reported that an inflammatory process induced by abdominal irradiation (Linard et al, 2003) is associated with an imbalance of the Th1/Th2 adaptive immune response that results in repression of genes involved in Th1 differentiation, cytokine responses (IFN␥) and migratory behavior (Grémy et al, 2006). Differentiation toward the Th2 pathway requires upregulation of endogenous feedback regulators such as suppressor of cytokine signaling (SOCS)-3 in several inflammatory models (Seki et al, 2003;Li et al, 2006), including abdominal irradiation (Grémy et al, 2006).…”
mentioning
confidence: 99%
“…Des modifications de la perméabilité vasculaire vis-à-vis des molécules et/ou de cellules jouent clairement un rôle fondamental dans la mise en place de la réponse inflammatoire. Pour conforter cette hypothèse, plusieurs études expérimentales rapportent une augmentation radio-induite de la libération de divers médiateurs (cytokines pro-inflammatoires, bio-amines, monoxyde d'azote) associée à une surexpression des molécules d'adhésion au niveau intestinal (Buell et Harding, 1989 ;Panès et al, 1995 ;Freeman et Mac Naughton, 2000 ;Linard et al, 2003). Ces arguments viennent renforcer l'idée avancée précédemment mettant en avant le rôle de l'hypoperfusion intestinale dans la libération massive de médiateurs inflammatoires : ceci pourrait avoir à la fois une incidence locale mais également sur des organes distants et viendrait illustrer le rôle clé que l'intestin peut jouer dans la mise en place du SDMV.…”
Section: Conséquences Des Variations De La Circulation Sanguine Et Lyunclassified